Efektivitas Skenario Lalu Lintas Arus Lebaran Idul Fitri di Gerbang Tol Sidoarjo berdasarkan Pemodelan Mikrosimulasi: Efektivitas Skenario Lalu Lintas Arus Lebaran Idul Fitri di Gerbang Tol Sidoarjo berdasarkan Pemodelan Mikrosimulasi - Radiansyah, Kusuma Aji; Isheka, Raihan Pasha; Aurarisa, Ilma (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2024)
On the eve of Eid al-Fitr 2023, there was an increase in the number of vehicles heading eastbound of Java Island through the Transjawa Toll Road from the normal traffic flow. The drastic increase in vehicle volume resulted in congestion at the Sidoarjo Tollgate. An effort to unravel the existing traffic congestion was to implement diversion and contraflow scenarios. This study was conducted to prove the most effective scenario to overcome transportation problems during the homecoming flow through microscopic simulations using PTV VISSIM software. In the diversion scenario, 35% of vehicles heading south will be diverted to exit through Sidoarjo 1 Tollgate. This scenario caused an increase in queue length by 34.66% and a delay of 28 seconds at Sidoarjo 1 Tollgate. On the other hand, with the same scenario, there is a decrease in queue length of 16.84% and a decrease in delay time of 58 seconds at Sidoarjo 2 Tollgate. Regarding average speed, there is a decrease of 18.24% on the road section after Sidoarjo 2 Tollgate due to merging. Under the contraflow scenario, there is no significant change in queue length and delay time at both gates, but there is an increase in the average speed of 62.22% at Sidoarjo 2 Tollgate. The simulation showed that the diversion scenario only moves the density of vehicles. In contrast, the contraflow scenario was an effective alternative to break down the density in the 2023 homecoming flow, as evidenced by the increased average speed.